Physico‐optical properties of a crosslinked hyaluronic acid scaffold for biomedical applications. Issue 35 (11th May 2017) - Lepore, Maria; Portaccio, Marianna; Delfino, Ines; Sironi, Laura; La Gatta, Annalisa; D'Agostino, Antonella; Izzo, E.; Schiraldi, Chiara
ABSTRACT: Optical techniques are increasingly employed for monitoring cell–matrix interactions in suitably prepared 3D scaffolds. The ability of designing and realizing synthetic extracellular matrix with well‐controlled optical properties is a crucial need in this field. For this purpose, a crosslinked hyaluronic acid (HA) scaffold is prepared. Fourier transform infrared and ultraviolet–visible spectroscopies enable to monitor the scaffold preparation process and to evidence scaffold high transparency and low fluorescence in the visible range. 3D optical characteristics of the HA scaffold are tested by two‐photon microscopy (TPM) imaging of embedded fluorescent microbeads and alive keratinocytes labeled with vital PKH67 dye at different depths from the scaffold surface. Some useful indications about the potentiality of TPM measurements for the determination of attenuation coefficient of turbid media are also reported. Moreover, the use of the presented HA scaffold for preparing tissue phantoms for fluorescence imaging or diffuse imaging is proposed. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45243. Abstract :